THE EFFECT OF THIN CAPITALIZATION, LIQUIDITY, PROFITABILITY, AND RELATED PARTY TRANSACTION ON TAX AGGRESSIVENESS IN INFRASTRUCTURE, UTILITY, AND TRANSPORTATION SECTOR COMPANIES IN THE 2021-2023 PERIOD - Addin , Umniyah; Biduri, Sarwenda (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to determine the Effect of Thin Capitalization, Liquidity, Profitability, and Related Party Transactions on Tax Aggressiveness in Infrastructure, Utilities, and Transportation Sector Companies. Method: This study uses quantitative data types with secondary data as the research data sources. The population is all Infrastructure, Utilities, and Transportation Sector Companies listed on the IDX in the 2021-2023 period, totaling 80 companies. The sample of this study uses purposive sampling so that the data used as a sample is 48 companies. This study uses multiple linear regression analysis techniques with SPSS version 27 data processing tools. Results: The results of the study show that Thin Capitalization has an effect on Tax Aggressiveness, Liquidity has an effect on Tax Aggressiveness, Profitability has an effect on Tax Aggressiveness and Related Party Transaction has an effect on Tax Aggressiveness. Novelty: This study provides a comprehensive analysis by simultaneously examining the impact of Thin Capitalization, Liquidity, Profitability, and Related Party Transactions on Tax Aggressiveness within the Infrastructure, Utilities, and Transportation Sector, which has been rarely explored in previous research.